Epistemic Violence and the Rise of the Pseudo‐Secular Islamic FBO in the Age of the 'Religious Turn' in Development. (20th March 2022) - Tittensor, David; Clarke, Matthew
Abstract: Over the past two to three decades, there has been a significant shift within the development sector. Previously considered 'taboo', religiously inspired Faith Based Organisations (FBOs) have become increasingly welcomed and involved as partners and collaborators with international financial institutions and leading aid donors. However, while a place has been set at the table this has not been an equitable one. Rather, there is still the expectation that religiously driven organisations will engage with the normative Western secular aid discourse that regards impartiality as sacrosanct. As a result, this has seen those FBOs that have chosen to participate develop hybridised‐identities, wherein we argue they have become pseudo‐secular in nature. Drawing on the literature, we note this development amongst well‐established Christian FBOs, such as World Vision, and extend our analysis to Islamic FBOs, with a case study of Islamic Relief. In doing so, we also argue that the hegemonic nature of the secular 'master narrative' imposed by the Western aid sector represents an instance of 'epistemic violence', and that FBOs should be able speak in their own terms.